Extreme elevation of ferritin and creatine kinase in primary infection with HIV-1. (January 2015) - Babiker, Zahir Osman Eltahir; Wingfield, Tom; Galloway, James; Snowden, Neil; Ustianowski, Andrew
The diagnosis of primary HIV-1 infection can be challenging, especially in the absence of reported risks or when presenting features are unusual and uncommon. We report an atypical case of primary HIV-1 infection with HIV-1 subtype C in a 61-year old Caucasian man who presented with extreme hyperferritinaemia without iron overload and marked elevation of serum creatine kinase without rhabdomyolysis. In view of his symptomatic seroconversion and low baseline CD4+ T-lymphocyte count, the patient was treated promptly with combination antiretroviral therapy. Subsequently, he made good clinical improvement on treatment and no opportunistic infections were diagnosed at presentation or as part of a later immune reconstitution syndrome. This novel case highlights the importance of clinical suspicion of HIV and suggests that primary HIV-1 infection should be considered in patients presenting with severe hyperferritinaemia or markedly elevated creatine kinase levels. Further studies are required to explain the causative biological mechanisms underlying this rare presentation.